Breast Cancer Knowledge and Attitude Toward Breast Cancer Screening Practice Among Catholic Nuns in Lake Zone—Tanzania - Gotfrida Marandu; Kija Malale; Rose Laisser; Joseph Mwanga; Peter Rambau (Breast Cancer: Basic and Clinical Research)
Background: Breast cancer poses a significant public health challenge in Tanzania. Limited knowledge about breast cancer and negative attitudes toward screening practices contributes to delayed diagnoses and poorer patient outcomes. Catholic nuns, who are often nulliparous, represent a population with an increased risk of developing breast cancer. Despite this risk, they remain an understudied group regarding breast cancer awareness and screening practices. Objective: This study aimed to assess breast cancer knowledge and attitudes toward screening practices among Catholic nuns residing in Tanzania’s Lake Zone. Study design: The study was a cross-sectional design. Methods: A total of 385 Catholic nuns participated in the study. To ensure a representative sample, nuns were chosen through simple random sampling, giving each Catholic nun an equal probability of being selected. Data were collected using a self-administered questionnaire and then analyzed using STATA version 18.0. Both descriptive and inferential statistics were used to draw conclusions. In inferential statistics, logistic regression was used to test for associations between categorical variables. The test statistics were considered significant when the P -value was less than .05 at a 95% confidence interval (CI). Results: This study enrolled 385 catholic nuns. 57.1% (95% CI, 52.0%-62.1%) of all surveyed catholic nuns had inadequate knowledge of breast cancer. Misconceptions also emerged as significant risk factors for inadequate knowledge. Thus, lack of awareness of breast cancer risk factors increased the odds by 5.57 times (adjusted odds ratio [AOR]: 5.57; 95% CI: 2.84-10.92; P  < .001). In addition, believing cancer was not inheritable (AOR: 2.65; 95% CI: 1.14-6.15; P  = .024), misperceiving oneself as being in a low-risk group (AOR: 1.65; 95% CI: 1.03-2.66; P  = .039), and underestimating the vulnerable age group (believing it is not above 40 years) (AOR: 2.60; 95% CI: 1.49-4.51; P  = .001) were all significantly associated with higher odds of inadequate knowledge. Regarding the attitude toward breast cancer screening practices, 62.3% (95% CI, 57.3%-67.2%) of the catholic nuns had negative attitudes. Conclusion: These findings highlight the need for breast health intervention educational programs to improve breast cancer awareness among Catholic nuns. Such programs should address risk factors, symptoms, screening methods, and treatment options, dispelling misconceptions. By empowering nuns with knowledge, they can make informed decisions about their health and take charge of their well-being.